2020
DOI: 10.15252/emmm.202012710
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐574 regulates FAM210A expression and influences pathological cardiac remodeling

Abstract: Aberrant expression of mitochondrial proteins impairs cardiac function and causes heart disease. The mechanism of regulation of mitochondria encoded protein expression during cardiac disease, however, remains underexplored. Here, we show that multiple pathogenic cardiac stressors induce the expression of miR‐574 guide and passenger strands (miR‐574‐5p/3p) in both humans and mice. miR‐574 knockout mice exhibit severe cardiac disorder under different pathogenic cardiac stresses while miR‐574‐5p/3p mimics that ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Both the host gene FAM114A1 and miR-574 expression is correlated (32). Thus, it is expected that FAM114A1 mRNA is induced in human and mouse MI and even aged murine hearts together with miR-574 (28)(29)(30)(31)(32). We have confirmed that FAM114A1 mRNA and protein expression is induced in human and mouse failing hearts compared to healthy hearts, especially in the activated MFs (Figure 1 and S1).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Both the host gene FAM114A1 and miR-574 expression is correlated (32). Thus, it is expected that FAM114A1 mRNA is induced in human and mouse MI and even aged murine hearts together with miR-574 (28)(29)(30)(31)(32). We have confirmed that FAM114A1 mRNA and protein expression is induced in human and mouse failing hearts compared to healthy hearts, especially in the activated MFs (Figure 1 and S1).…”
Section: Discussionsupporting
confidence: 63%
“…FAM114A1 is a host gene for miR-574 and shares the common promoter with embedded intronic miR-574 (31, 32). Both the host gene FAM114A1 and miR-574 expression is correlated (32).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations